Pendekatan guru dalam meningkatka minat belajar siswa pada mata pelajaran bahasa Arab di Mts a'mal iqomah seri tanjung : Pendekatan guru dalam meningkatka minat belajar siswa pada mata pelajaran bahasa Arab di Mts a'mal iqomah seri tanjung - ira sapira (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2025)
This study explores the level of student interest in learning Arabic, the teaching strategies employed by teachers, and the challenges encountered in learning at MTs A???mal Iqomah Seri Tanjung. Utilizing a qualitative approach, the research involved observation, interviews, and documentation methods. The findings reveal the following: 1) There is a range of student interest in learning, with most learners exhibiting high enthusiasm, while others display lower motivation. 2) Teachers implement a variety of educational strategies, such as inquiry-based methods, lectures, discussions, affective approaches, interactive learning media, and project-based activities, to sustain student engagement. 3) Teachers face several challenges, including a lack of environmental support, the predominance of Indonesian language use, passive teaching methods, and minimal awareness regarding the importance of Arabic. This study provides valuable insights into the learning environment at MTs A???mal Iqomah and offers recommendations for enhancing learning effectiveness and student interest by fostering more creative and relevant teaching strategies.